Software de control de aforos y potreros en la unidad de producción de pastos y forrajes de la carrera de pecuaria de la ESPAM MFL - López Mora, Wilson Fabián (2013)
The objective of this study was to develop software for measurement and foraging control in the career of animal science in the ESPAM - MFL to record management and process control. The realization of this software started with filing a diagnosis of the problems in the Production Unit of Pastures and Forages (UPPF), then keeping track of forage in pastures, then proceeded to search and implement possible solutions for the creation of a system to ease the controls and meet the educational qualifications required. It was necessary the application of another method like the inductive-deductive allowing observation of the manual system, method for preparing the system, in this case consisted of the application of the rapid development (DRA, Rapid Development Model), thereby providing a system that meets the needs identified, allowing a technical and dynamic way to have control of the information. Interviews were conducted with managers of Pastures and Forages Unit, which allowed us to know in detail the system used before, obtaining information for effective data processing software. The developed system ease the UPPF process entering few data in reliable records obtained for the general management of the forages and field pasture.